Neuroscience and psychoanalysis: talking about autism - da Rosa Vilani, Marina; Port, Ilvo Fernando (Clinical Styles. The Journal on the vicissitudes of childhood, 2018)
Based on an integrative understanding between Psychoanalysis and Neurosciences, this work aims to comprehend etiology of autism. This is a narrative literature review that includes data from the history and concept of autism through a qualitative exploratory research in databases, periodics and books. Despite the disparities on the etiology and treatment between these fields, some studies led to the conclusion that, when a child is born with organic vulnerabilities, they may affect the exercise of parental functions. Thus, either a potentialization may occur, or the appearance of autistic traits in both the psychic and also the neurobiological scope, since the individual is in the process of organic development concomitant with subjectivity.